Legal optic on digitalization of cultural heritage through e-tourism and e-government to back up ecotourism in greater Malang Indonesia - Sukardi, Sukardi; Fadli, Moh; Puspitawati, Dhiana; Maharani, Diah Pawestri; Luthfi, Mustafa (Legality : Jurnal Ilmiah Hukum, 2022)
This research aims to gain a vivid and comprehensive portrait of legal aspects in the digitalization of cultural heritage in Greater Malang in Indonesia from the perspective of ecotourism and the state’s role in terms of policies and involvement of the members of the public in cultural conservation. The involvement of e-tourism and e-government in managing and developing the tourism potential in developed areas is inevitable. Cultural heritage-based tourism promoting the utilization of advanced information and communication technology has attracted the attention of tourists. Empirically, the digitalization of cultural heritage does not stand on its own but is more integrated with other aspects and sectors. The proposed concept in this study reminds us of the urgency in the development and utilization of integrated cultural heritage digitalization from the perspectives of eco-tourism, e-tourism, as well as other sectors such as e-government and spiritual aspect. The process of the development and utilization of digitalization of cultural heritage tourism is intended to ward off any disputes over ulayat rights happening these days. The role of the government and the participation of tribal people are deemed vital in reconstructing the system of social and spiritual values in developing eco-tourism based on the application of an integrated digital information system disseminating local wisdom through the threshold of global civilization.